Thromboxane A2 Receptor Stimulation Enhances Microglial Interleukin-1β and NO Biosynthesis Mediated by the Activation of ERK Pathway - Yang, Wanlin; Yan, Aijuan; Zhang, Tingting; Shao, Jiaxiang; Liu, Tengyuan; Yang, Xiao; Xia, Weiliang; Fu, Yi (Frontiers in Aging Neuroscience, 2016)
Abstract Background and Purpose: Thromboxane A2 (TXA2) receptors (TP) interact with the ligand TXA2 to induce platelet aggregation and regulate hemostasis. Recently TP-mediated signaling has been suggested to function in multiple cell types in the brain. In this report, we aim to study the expression and physiological role of TP in microglia, in particular after brain ischemia. Methods: Ischemic brain sections were analyzed for TP expression. Microglial cell line and primary microglia were cultured, or neuronal cell line co-culture system was used to determine the TP mediated signaling in inflammation and microglia activation. Results: We found that the TP level was significantly increased in ipsilateral mouse brain tissue at 24 h after ischemia-reperfusion, which was also found to partly co-localize with CD11b, a marker for microglial and infiltrated monocyte/macrophage, in peri-infarct area. Immunofluorescence staining of primary microglia and microglial cell line BV2 revealed the predominant membrane distribution of TP. Conditioned culture media from TP agonist U46619-treated BV2 cells decreased neuronal SH-SY5Y cell viability and induced apoptotic morphological changes. Furthermore, U46619 enhanced IL-1β, IL-6 and iNOS mRNA expression as well as IL-1β and NO releases in BV2 cells or primary microglia. Such stimulation could be attenuated by TP antagonist SQ29548 or MEK inhibitor U0126. The dose- and time-dependent extracellular-signal-regulated kinase (ERK) phosphorylation induced by U46619 further demonstrated ERK signaling-mediated microglia activation by TP agonist. Conclusions: This study has shown a novel role of TP in microglia activation via the ERK signaling pathway, which provides insights for the management of neuroinflammation in diseases like cerebral infarction.